中国境内通古斯人群的体型 - 胡荣; 温有锋; 王先明; 杨洋; 刘素伟 (2017)
体型是对身体形状和组成成分的描述,影响人的生理机能、运动素质、心理情感、职业选择等多方面,可帮助评价个体生长发育状况并指导健康成长,因而具有重要; 的实际意义。通古斯族群的起源、迁移及各民族之间亲缘关系问题历来为学者所关注和争论。本研究在辽宁、黑龙江、和内蒙古自治区随机抽取辽宁满族、黑龙江满; 族、鄂伦春族、鄂温克族、赫哲族成人人群(男女皆有)进行Heath-Carter法体型研究,探讨中国境内通古斯人群的体型特点及规律,为分析中国境内; 通古斯人群的亲缘关系提供体质人类学方面的证据。 Somatotype analysis involves the description about body shape and; composition, which can affect, for example, physical function, sport; capabilities, mental emotions, and career choice. Additionally; somatotype can help in evaluating an individual's growth and; development, leading them to healthy growth. There have always been; debates about the origin, migration, and kinship of the Tunguska. This; paper uses the Heath-Carter somatotype method for the Liaoning Manchu,; Heilongjiang Manchu, Oroqen, Ewenki, and Hezhen adults (both males and; females) who were chosen randomly from the autonomous regions of; Liaoning, Heilongjiang and Inner Mongolia. This study discusses these; somatotype characteristics of the Tunguska and analyzes the kinship of; this group in China.